ANALISA TINGKAT KEBISINGAN DI ARENA PERMAINAN BEBERAPA MALL DAERAH ISTIMEWA YOGYAKARTA MENGGUNAKAN SOFTWARE VISUAL ANALYSER DAN SOUND LEVEL METER - , DIAN ALVIANI SUKMA RIZKI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Game zone is one places that can cause noise. The noise could potentially affect comfortable and health of public. Therefore, the action was necessary to measure and determine the level of noise that occurs in the game zone. The level of continuous noise measurement of game zone several malls around DIY have been conducted on Juli until September 2013. The noise in game zone comes from sound of music and voice of visitor. The purpose of this research was to measure level of continuous noise in the game zone several malls, so it can be taken further against to the noise that happen. The tools used for measuring the intensity of the noise in the arena game is a sound level meter Lutron SL-4012 and software visual analyzer 2011. Sampling was carried out based on variations of the day and variations in time (hours). Based on the analysis of the research has been done, the level of continuous noise that occurs in the game zone several malls Daerah Istimewa Yogyakarta average was above 85 dB (A),it indicates the level of noise going on in the gaming arena has exceeded the threshold limit value has been determined by the Minister of Health and Minister of the Environment.